KELIMPAHAN DAN KARAKTERISTIK BAKTERI DALAM BAKASANG BIA GARU (Tridacna gigas L) [Abundance and Characteristics of Bacteria in Bakasang Bia Garu (Tridacna gigas)] - Mahulette, Ferymon; Pattipeilohy, Mery; Pelamonia, Alamanda (BRIN Publishing (Penerbit BRIN), 2023)
Bakasang bia garu is a clam-based fermented product processed by the people of the Babar Islands, Maluku. Uncontrolled processing allows the presence of unwanted bacteria in these local food products. Preservatives added in the processing of bakasang bia garu are very diverse. This study aims to isolate and characterize lactic acid, halotolerant, and coliform bacteria from bakasang bia garu which are processed using different preservatives. Lactic acid bacteria were isolated using de Man Rogosa and Sharpe Agar (MRSA) media while halotolerant and coliform bacteria used Mannitol Salt Agar (MSA) and Eosin Methylene Blue Agar (EMBA) media, respectively. Characterization was carried out macroscopically and microscopically. The results showed that lactic acid bacteria were only found in bakasang with synthetic salt and vinegar preservatives of 3.5x103 CFU/g which was dominated by Pediococcus pentosaceous. Halotolerant and coliform bacteria have diverse characteristics that belong to the genera Staphylococcus, Escherichia, and Enterobacter. Bakasang bia garu needs to optimize its controlled processing to improve the quality of this local food product in the future